2016
DOI: 10.1007/s00127-016-1183-x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use, mental well-being, self-esteem and general self-efficacy among final-year university students

Abstract: We observed that higher levels of drinking were associated with small, yet statistically significant, differences in psychological outcomes for men and women. Our findings are of uncertain clinical significance; however, they underscore the importance of investigating a fuller range of social and personality factors that may confound the association of drinking and psychological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 48 publications
3
27
1
1
Order By: Relevance
“…Two previous studies conducted in large samples have generated inconclusive results in relation to alcohol consumption. While alcohol use was linked to lower mental wellbeing in the UK general population [37] and among students in New Zealand [38], the latter study found that heavy drinking was correlated with high self-esteem in males and low self-esteem in females. The study conducted in New Zealand also reported higher self-efficacy in males and females who drank alcohol.…”
Section: Discussionmentioning
confidence: 84%
“…Two previous studies conducted in large samples have generated inconclusive results in relation to alcohol consumption. While alcohol use was linked to lower mental wellbeing in the UK general population [37] and among students in New Zealand [38], the latter study found that heavy drinking was correlated with high self-esteem in males and low self-esteem in females. The study conducted in New Zealand also reported higher self-efficacy in males and females who drank alcohol.…”
Section: Discussionmentioning
confidence: 84%
“…However, some research has suggested that students who drink more frequently might be more likely to engage in the academic environment and elicit social support ( Borsari & Carey, 2006 ). Molnar, Busseri, Perrier, and Sadava (2009) found a prospective relationship between alcohol use and higher levels of subjective well-being among college students, and Blank, Connor, Gray, and Tustin (2016) found increased self-efficacy among college students who consumed alcohol. Existing longitudinal studies have found paradoxical effects between alcohol use and education ( Crosnoe & Riegle-Crumb, 2007 ; Patrick, Schulenberg, & O'Malley, 2016 ), highlighting the complex relationship between alcohol use and academic success and calling for increased research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, alcohol use frequency before enrollment was positively associated with the odds of graduate degree completion (adjusted odds ratio = 1.007) [43]. Students who drink might be more likely to engage in the academic environment and stimulate social support [77], particularly as there were prospective relationships between alcohol use and higher subjective well-being and increased self-efficacy [78,79] among students. Compared to sober peers, students consuming moderate to high levels of alcohol and low marijuana demonstrate lower GPAs, but this difference became non-significant over time [71,80].…”
Section: Discussionmentioning
confidence: 99%